Kalman Silvert América Latina y la construcción de la democracia - Lowenthal, Abraham F.; Weinstein, Martin (Latin America Research Commons, 2021)
The life of Kalman Silvert illustrates the extraordinary career of an extraordinary man, one of the founding architects of Latin American studies in the United States, an important builder of the inter-American academic community, and an influential figure in relations between the United States and Latin America. Thirteen distinguished Latin Americanists elaborate on Silvert's role as an academic, teacher, mentor, colleague, public intellectual, institution builder and philanthropist. They also emphasize his contributions to the Ford Foundation, where he served as Senior Program Advisor from 1967 until his death in 1976. Co-editors Abraham F. Lowenthal and Martin Weinstein frame the retrospective, underscoring the integration of Silvert's multiple contributions and the permanent relevance of his legacy.